APPRAISAL OF INTERACTION AMONG NIPPING AND CHICKPEA (CICER ARIETINUM L.) GENOTYPES AND THEIR CORRELATED RESPONSE FOR GRAIN YIELD - H. Khan; R. Gul; N. U. Khan (Journal of Animal and Plant Sciences, 2017)
Nipping is considered to be the cause of increase in seed yield of chickpea. Whether, either morphs of chickpea (Desi & Kabuli) verify this statement or not, an experiment was carried out using twenty chickpea genotypes (11 Desi & 9 Kabuli) and two treatments (nipped, control). Two nippings were carried out with 20-25 days interval. Data analysis revealed highly significant differences among genotypes, treatments and genotype by nipping interaction for yield and yield attributing traits. Eight genotypes viz, NDC-4-20-3, NIFA-2005, Karak-2, SL-3-15, NKC-5-S-12, Karak-1, NDC-15-1 and SL-3-64 revealed positive response to nipping, which also provides green forage. Whereas, twelve genotypes including 3 Desi and 9 Kabuli genotypes showed disincline to nipping. It is concluded that nipping should not be practised without prior testing of its effect on genotypes.  Moreover, Desi chickpea respond positively as compare to Kabuli chickpea. Seed yield plant-1 showed highly significant and positive genotypic and phenotypic correlation with secondary branches plant-1 (rg = 0.54,rp = 0.46), pods plant-1 (rg = 0.89,rp = 0.83), seeds pod-1 (rg = 0.58,rp = 54), biological yield plant-1 (rg = 0.97,rp = 0.92), 100-seed weight (rg = 0.52,rp = 0.53), suggesting these traits to be used as selection criteria for yield improvement.
Keywords: Chickpea; genotypes; nipping; correlation; yield